Anaerobic Fermentation of Kepok Banana (Musa Paradisiaca) Peels with Different Levels of Tapioca for Reducing Their Fiber Components - Koni, Theresia Nur Indah; Tori, Lodofikus; Foenay, Tri Anggarini Yuniawati (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
Banana peel is restricted to use as feedstuffs because it has a high crude fiber content. The reduction of crude fiber can be done by anaerobic fermentation such as silage making. Soluble carbohydrates are needed as an energy source for microorganisms in ensilage process. Tapioca is one of soluble carbohydrates that can be used to improve silage quality. The objective of this study was to evaluate effect of tapioca levels on the fiber fraction of kepok banana peel silage (Musa paradisiaca). A completely randomized design was used in this study, with 4 treatments and 5 replications, namely T0: without tapioca, T5: 5% tapioca, T10: 10% tapioca, T15: 15% tapioca. Variables observed were the content of NDF (%), ADF (%), hemicellulose (%), cellulose (%), and lignin (%).Collected data was analyzed by analysis of variance and if it had a significant effect, it was continued with Duncan's multiple range test. The results of analysis of variance showed that the level of tapioca had a highly significant effect (P<0.01) on NDF, ADF, hemicellulose, cellulose, and lignin. DMRT showed that the lowest NDF content was at T15 with an average of 48.06%, the lowest ADF was found at T15 with an average of 20.20%, the lowest hemicellulose was found at T15 with an average of 27.46%, the lowest cellulose was found at T10 with an average of 7.98% and the lowest lignin against T15 with an average of 12.09%. In conclusions, 1) Different levels of tapioca was can reduce ADF, NDF, hemicellulose, cellulose, and lignin in kepok banana peel silage, 2) The use of 10% tapioca reduced the highest kepok banana peel silage fiber fraction.